ZigBee Wireless Dynamic Sensor Networks: Feasibility Analysis and Implementation Guide - Oliveira, Thiago de Almeida [UNESP]; Godoy, Eduardo Paciencia [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2016)
The wireless sensor network (WSN) technology has attracted increasing attention considering its potential in many application fields. In most studies on WSNs, the network is assumed to cover several static devices over a fixed coverage area. As an extension of WSN capabilities, the devices mobility and the network dynamism provide a new chain of interesting applications defined as wireless dynamic sensor network (WDSN). The initial challenge in the WDSN is to investigate whether this dynamic imposed on the network will be supported, once the used network protocol must meet the requirements for WDSN applications, such as network formation and self-organization, route discovery and communication management with the input and output of devices on the network. In order to overcome these issues, specific wireless protocols have been developed to meet the applications with device mobility in the WSN. However, these specific protocols limit the development of the WSDN since, they are isolated and proprietary solutions, instead of using a standardized protocol for interoperability. This paper presents a feasibility analysis of the ZigBee protocol for the WDSN applications. A survey of application features and requirements, as well as a discussion of advantages and limitations, regarding the adoption of the ZigBee protocol in the WDSN is presented. An implementation guide for the ZigBee WDSN is proposed in order to assist a new application of this technology. Furthermore, a proof of concept using ZigBee devices validates the implementation guide and proves the ZigBee WDSN feasibility.
Keywords: Wireless dynamic sensor networks; ZigBee protocol; MANET